LEGACY IN DIFFERENT RELIGION AND THE IMPLEMENTATION OF WAJIBAH HERITAGE AGAINST NON MOSLEM HEIR IN INDONESIAN - I Nyoman Sujana (Warmadewa Press, 2020)
This study examines more deeply about the judge's consideration in establishing a Muslim as an heir of the assets of a non-Muslim heir in Indonesia, and why wajibah must be chosen as a solution in providing inheritance to non-Muslim heirs in Indonesia. This research is a normative legal research by using statute approach conceptual approach and case approach. The result showed that firstly the judges' considerations that deviate from the Word of the Prophet (peace be upon him):